Scheduling Analysis of Oil Tank Maintenance Project System Coil Heater Pipe Factory Using CPM Method (Critical Path Method) and PERT (Project Evaluation and Review Technique) - Hanifa, Putri; Megawati, Liya; Wahidin, Wahidin (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
Scheduling is a crucial part of every project since it influences so many aspects. In spite of the fact that the project isn't wrapping up when it was supposed to, the corporation is sticking to the provided timetable and running into trouble as a result. In this case, the CPM and PERT methodologies will be used to calculate and schedule the project's crucial trajectory in order to foresee any delays in the project's completion. The findings of the analysis show that the activities A through L make up the critical route for one tank's worth of labor, and that the CPM and PERT approaches provide different conclusions. Which, via the use of the CPM approach, cut down the typical project duration of 24 days to 20 days of actual labor time. Meanwhile, the PERT technique shows that a two-hour reduction in the typical project duration—from 24 days to 23 days and six working hours—is possible in 70% of cases.